Mobile Apps for Improving Mental Health in Teens and Young Adults - I. V. Gribkova (Здоровье мегаполиса, 2025)
Background. Adolescence and young adulthood are key stages for the onset of mental disorders and health-related behaviors. Poor mental health during this period can seriously affect a young person’s chances in later life and have a significant negative impact on physical health, education and employment in later life. Meanwhile, the deterioration of mental health in young people, especially students, is observed on a global scale. These problems significantly contribute to disability rates worldwide and create a high economic burden. Therefore, adolescents and young adults are an important group in urgent need of preventing poor mental health. However, successful implementation of psychological support programs remains challenging due to limited availability of treatment options, high costs, and the underestimation of the impact of youth stress. Digital health methods, such as smartphone apps, have the potential to address this issue. Materials and methods. This review describes current work examining mobile apps for improving mental health in young people that use evidence-based methods and have been shown to be highly effective in robust, well-designed randomized controlled trials. Results. The information presented can help develop and perfect digital technologies for improving mental health in young people.